2000
DOI: 10.4188/jte.46.7
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Thickness Relation and Compression Mechanism of Plain and Rib Knitted Fabrics

Abstract: In this work, pressure-thickness relation is investigated for a series of plain and rib knitted structures made from cashmere and polyester textured (PET) yarns. The pressure-thickness curve during lateral compression is divided into three regions, namely, the first linear region followed by the non-linear region and second linear region [1]. The portion of these regions and also the slopes of the linear regions are found to differ markedly by knit construction and yarn structure for knit fabrics. A comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The compressibility behavior of knitted and woven fabrics depends on a number of factors, that is, fabric tightness, fabric surface irregularity, yarn hairiness, yarn compressibility, fiber material etc. The analyses of the pressure-thickness relationship performed by Alimaa et al [29] demonstrated a very prominent effect in terms of the knit construction and yarn structure. It was observed that fabric compressibility primarily depended on the fiber material.…”
Section: Compression Resistancementioning
confidence: 98%
See 1 more Smart Citation
“…The compressibility behavior of knitted and woven fabrics depends on a number of factors, that is, fabric tightness, fabric surface irregularity, yarn hairiness, yarn compressibility, fiber material etc. The analyses of the pressure-thickness relationship performed by Alimaa et al [29] demonstrated a very prominent effect in terms of the knit construction and yarn structure. It was observed that fabric compressibility primarily depended on the fiber material.…”
Section: Compression Resistancementioning
confidence: 98%
“…The composition properties of knitted fabrics were also essentially due to their knit constructions. Moreover, the loop length determined the compressibility of knitted fabrics to a great extent [29].…”
Section: Compression Resistancementioning
confidence: 99%
“…This can be explained by a structure of loops, which leads to decreasing compression resilience, and compression energy as the loop space becomes smaller [3]. In addition, the factors that influence knitted fabric's compressibility are structural parameters, loop length and cover factor as well as raw material and fibres blend ratio [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Compressibility is an important property of fabrics which has been investigated from various aspects for some time [7][8][9][10][11][12]. It is of major importance when assessing the fabrics' suitability for medical use.…”
mentioning
confidence: 99%